1993
DOI: 10.1192/bjp.163.4.492
|View full text |Cite
|
Sign up to set email alerts
|

Familial Psychiatric Illness and Obstetric Complications in Early-Onset Affective Disorder

Abstract: Early-onset affective disorder is associated with obstetric complications and a high familial risk of psychiatric illness, in particular psychosis. In a matched case-control study, we investigated 47 adult in-patients with major depressive disorder or bipolar 1 disorder, who had earlier in life presented to a child psychiatry department. Cases were matched on sex, social class and ethnic group with 47 controls, who were admitted to hospital for affective disorders in adult life but had no psychiatric contact b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 21 publications
(10 reference statements)
2
27
0
1
Order By: Relevance
“…On the other hand, obstetrical complications could have an "anticipatory effect" (possibly determining early presentation of psychiatric disorders in subjects with a predisposition to mental illness), as demonstrated by the earlier age at onset in this group. It seems that obstetrical complication can give an adjunctive vulnerability to develop earlier psychiatric disorders, confirming previous findings outlined in patients with schizophrenia or mood disorders (Guth et al, 1993;Kotlicka-Antczak et al, 2001). In this way, future research could investigate the role of obstetric complications in subjects with high risk of psychosis in terms of their impact on probability and time to transition to a full-blown psychotic disorder…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, obstetrical complications could have an "anticipatory effect" (possibly determining early presentation of psychiatric disorders in subjects with a predisposition to mental illness), as demonstrated by the earlier age at onset in this group. It seems that obstetrical complication can give an adjunctive vulnerability to develop earlier psychiatric disorders, confirming previous findings outlined in patients with schizophrenia or mood disorders (Guth et al, 1993;Kotlicka-Antczak et al, 2001). In this way, future research could investigate the role of obstetric complications in subjects with high risk of psychosis in terms of their impact on probability and time to transition to a full-blown psychotic disorder…”
Section: Discussionsupporting
confidence: 84%
“…Obstetric complications appear to be more related to specific bipolar subtypes such as the early-onset (Guth et al, 1993) or psychotic ones (Hultman et al, 1999). Alternatively, only specific obstetric complications are associated with an increased risk of future bipolar disorder: a recent paper found that children delivered by planned caesarean section had a 2.5-fold increased risk of bipolar disorder (Chudal et al, 2014), while another paper found a 2.7-fold increased risk in case of preterm birth (Nosarti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical or population based studies have found that such characteristics distinguish childhood onset from adult onset affective disorders (Guth et al, 1993;Jaffee et al, 2002;van Os et al, 1997), differences in methodologies and samples may partly account for the inconsistent results. In our sample, early childhood characteristics also were unrelated to the severity of first MDD episode, despite Vocisano et al (1996) finding a link between obstetric complications and severity of affective illness in adulthood.…”
Section: Discussionmentioning
confidence: 95%
“…For example, according to Preti et al, (2000), adult patients with histories of mood disorder had significantly lower birth weight (for their gestational ages) than did matched normal controls. Guth et al (1993) found that obstetric complications were more common among cases with early-onset mood disorder than among those with late-onset. And Vocisano et al, (1996) reported that inpatients with prolonged, severe, and functionally impairing MDD had higher frequencies of birth related problems and physical disorder in infancy than did less severely depressed outpatients.…”
mentioning
confidence: 97%
See 1 more Smart Citation